2013
DOI: 10.5545/sv-jme.2012.1002
|View full text |Cite
|
Sign up to set email alerts
|

Polypropylene/Clay Nanocomposites Produced by Shear Controlled Orientation in Injection Moulding: Deformation and Fracture Properties

Abstract: The effect of distinct morphologies induced by shear controlled orientation in injection moulding (SCORIM) in the mechanical and fracture performance of polypropylene (PP) and PP/nanoclay mouldings is examined in this work. The effect of high shear conditions applied during processing was assessed. Samples exhibited a range of fracture stability ranging from a modest non-linearity to a quasi-stable regime depending on material type and injection conditions. Neat PP showed non-linear brittle behaviour while nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…12 Mechanical properties such as deformation and fracture showed that despite the fracture has started at practically the same loading level, the propagation energy varied with processing conditions and nanoclay content. 13 Thermal, morphological and thermo-mechanical properties were investigated, where it was observed that melting temperature (T m ) and crystallinity degree (X c ) were not affected while thermal stability increased. 14 Otherwise, Ataeefard and Moradian 15 observed improvement of mechanical properties, decreasing of crystallinity degree and the presence of intercalated/exfoliated structures in PP/organoclay nanocomposites.…”
Section: Introductionmentioning
confidence: 99%
“…12 Mechanical properties such as deformation and fracture showed that despite the fracture has started at practically the same loading level, the propagation energy varied with processing conditions and nanoclay content. 13 Thermal, morphological and thermo-mechanical properties were investigated, where it was observed that melting temperature (T m ) and crystallinity degree (X c ) were not affected while thermal stability increased. 14 Otherwise, Ataeefard and Moradian 15 observed improvement of mechanical properties, decreasing of crystallinity degree and the presence of intercalated/exfoliated structures in PP/organoclay nanocomposites.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of the intercalation or exfoliation of the organoclays in the polymer extrusion process has been extensively studied [14][15][16]. The degree of intercalation and dispersion is affected by the organoclay chemistry [17] and the screw design [18,19] in the polymer extrusion process.…”
Section: Introductionmentioning
confidence: 99%